ChemInform Abstract: Copper‐Catalyzed Multicomponent Click Synthesis of 5‐Alkynyl 1, 2, 3‐Triazoles under Ambient Conditions. Issue 2 (9th January 2013) - Alonso, Francisco; Moglie, Yanina; Radivoy, Gabriel; Yus, Miguel
Abstract The simple and efficient procedure allows the preparation of a broad spectrum of fully substituted triazole structures.